Grape seed powder improves renal failure of chronic kidney disease patients - Turki, Khaoula; Charradi, Kamel; Boukhalfa, Habib; Belhaj, Monia; Limam, Ferid; Aouani, Ezzedine (Technische Universität Dortmund, 2016)
Chronic kidney disease (CKD) is a syndrome characterized by progressive and irreversible deterioration of renal function linked to slow destruction of renal parenchyma, eventually terminating in death when sufficient number of nephrons are damaged. Oxidative stress is commonly observed in CKD patients resulting from an imbalance between overproduction of reactive oxygen species (ROS) and impairment of defence mechanisms. Grape seed extract (GSE) is a polyphenolic mixture exhibiting antioxidant and anti-inflammatory properties. We conducted an interventional pilot study of supplementation with GSE capsules (GSE group, n = 23) or placebo (control group, n = 10) on CKD patients. Blood and urine samples were collected at baseline and after a six-month-long supplementation period to determine some renal function biomarkers, as well as antioxidant, anti-inflammatory and haematological parameters. GSE improved glomerular filtration rate (GFR) and proteinuria, increased the anti-oxidant status as assessed by high plasma catalase and superoxide dismutase and also lowered lipoperoxidation and carbonylation. GSE ameliorated inflammation by decreasing CRP, triglyceridemia and counteracted anemia and thrombocytopenia. Supplementation with 2 g GSE/day for six months improved some kidney function parameters of CKD patients and this beneficial effect of GSE seems to be mediated at least partly by its antioxidant and anti-inflammatory properties.
EXCLI Journal;Vol. 15, 2016
Keywords: grape seed extract; oxidative stress; antioxidant status; chronic kidney disease; protection; 610